2012
DOI: 10.5195/ijt.2012.6105
|View full text |Cite
|
Sign up to set email alerts
|

Overview of States' Use of Telehealth for the Delivery of Early Intervention (IDEA Part C) Services

Abstract: Background:Early intervention (EI) services are designed to promote the development of skills and enhance the quality of life of infants and toddlers who have been identified as having a disability or developmental delay, enhance capacity of families to care for their child with special needs, reduce future educational costs, and promote independent living (NECTAC, 2011). EI services are regulated by Part C of the Individuals with Disabilities Education Improvement Act (IDEA); however, personnel shortages, par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
58
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(61 citation statements)
references
References 8 publications
1
58
0
2
Order By: Relevance
“…In a recent study of occupational therapists in rural NSW, while the therapists used digital technology for their personal networks and professional development, there was limited use of technology for therapy provision. The reported barriers related to age and technology preferences of the provider, but equally important were issues of limited internet connectivity, training and support as well perceptions about lack of acceptance by clients [53]. As digital technology becomes more accessible both in relation to bandwidth and accessibility through the major telecommunication reform under the aegis of the national broadband network (NBN) program, this barrier is likely to become less of an impediment for service provision both by providers and end-users in rural Australia.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In a recent study of occupational therapists in rural NSW, while the therapists used digital technology for their personal networks and professional development, there was limited use of technology for therapy provision. The reported barriers related to age and technology preferences of the provider, but equally important were issues of limited internet connectivity, training and support as well perceptions about lack of acceptance by clients [53]. As digital technology becomes more accessible both in relation to bandwidth and accessibility through the major telecommunication reform under the aegis of the national broadband network (NBN) program, this barrier is likely to become less of an impediment for service provision both by providers and end-users in rural Australia.…”
Section: Discussionmentioning
confidence: 97%
“…A study by Tindall and Huebner [51] looked at speech therapy delivered by videophones and found that this method alleviated some of the burden of providing care, and produced similar results to face to face consultations. However, the use of digital technology is still limited by educational barriers and socioeconomic status [52,53]. In a recent study of occupational therapists in rural NSW, while the therapists used digital technology for their personal networks and professional development, there was limited use of technology for therapy provision.…”
Section: Discussionmentioning
confidence: 98%
“…In rural communities, children with developmental disabilities often lack appropriate services and supports or are underserved (Cason, Behl, & Ringwalt, ; Hebbeler, Spiker, & Kahn, ; Koegel et al, ; Terry, ; Wacker et al, ). Children with developmental disabilities who engage in serious challenging behavior and reside in rural communities may be at a double disadvantage.…”
mentioning
confidence: 99%
“…61 Postimplantation therapies like parent training, auditory training, speech and language therapy, counseling, and communication strategy training have been successfully implemented in rural areas of Australia, but telerehabilitation carries risks associated with confidentiality and security, and concerns about quality and demonstrated effectiveness of services, reimbursement, and maintaining technology infrastructure. 62 Early intervention typically is provided in the home or at daycare. Providing home-based services to older children and adults might increase enrollment and compliance with treatments and reduce travel costs by patients.…”
Section: Habilitation and Rehabilitation Servicesmentioning
confidence: 99%